2017
DOI: 10.1007/978-3-319-64206-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Extraction of Typological Linguistic Features from Descriptive Grammars

Abstract: Linguistic typology is an area of linguistics concerned with analysis of and comparison between natural languages of the world based on their certain linguistic features. For that purpose, historically, the area has relied on manual extraction of linguistic feature values from textural descriptions of languages. This makes it a laborious and time expensive task and is also bound by human brain capacity. In this study, we present a deep learning system for the task of automatic extraction of linguistic features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, they are often extremely time-consuming to design, and require the data they analyse to be cleaned and formatted in particular ways, which can also be quite labour-intensive. Moreover, currently available techniques have proven to be ineffective even for tasks that might seem most amenable to such an approach, such as the extraction of typological linguistic information from published grammars (Virk et al, 2017 ). This may change in coming decades as artificial intelligence becomes more powerful and flexible (Virk et al, 2017 ), but for the moment, the need for human coders is unavoidable even when it comes to these more tractable cases.…”
Section: Converting Qualitative To Quantitative: Choosing An Appropri...mentioning
confidence: 99%
“…However, they are often extremely time-consuming to design, and require the data they analyse to be cleaned and formatted in particular ways, which can also be quite labour-intensive. Moreover, currently available techniques have proven to be ineffective even for tasks that might seem most amenable to such an approach, such as the extraction of typological linguistic information from published grammars (Virk et al, 2017 ). This may change in coming decades as artificial intelligence becomes more powerful and flexible (Virk et al, 2017 ), but for the moment, the need for human coders is unavoidable even when it comes to these more tractable cases.…”
Section: Converting Qualitative To Quantitative: Choosing An Appropri...mentioning
confidence: 99%
“…Previously, a few experimental techniques and associated systems have been reported for automatic extraction of typological information. In (Borin et al, 2018;Virk et al, 2017), the authors have reported on simple pattern matching and syntactic parsing based systems. The systems have modest accuracy and recall and are very restricted with respect to the number of features they can target.…”
Section: Related Workmentioning
confidence: 99%
“…Given its novelty, only a few embryonic approaches (Virk et al, 2019;Wichmann and Rama, 2019;Macklin-Cordes et al, 2017;Hammarström, 2013;Virk et al, 2017) have addressed the task so far. Of these, some are word-based and some combine words with more elaborate analyses of the source texts such as frame-semantics (Virk et al, 2019).…”
Section: Introductionmentioning
confidence: 99%